The effect of wear of a cutting tool with a controlled depth of cut on the acoustic Emission - Филоненко, Сергей Федорович (Eastern-European Journal of Enterprise Technologies, 2015)
Control over the depth of cut when the composite-material tool wears is an important task in providing the desired size of the manufactured products. The task is solvable due to research that uses the method of acoustic emission. We have modeled the acoustic emission signals in the process of machining a composite material at a controlled depth of cut with regard to the machining tool deterioration. It is determined that an increasing wear of the machining tool at a constant cutting depth expands the acoustic emission amplitude. However, the increase in the average level of the signal amplitude of the acoustic emission is ahead of the increase in its standard deviation and variance. The findings indicate that analysis of the average amplitude rate of the acoustic emission signal can be used in methods of control over the machining of composite materials and the depth of cut with regard to the wear of the machining tool.